Ruling the Interregnum: Politics and Ideology in Nonhegemonic Times. (September 2019) - Stahl, Rune Møller
This article offers reinterpretation of the current economic and political crisis through the lens of Gramsci's concept of "interregnum, " departing from the model of "punctured equilibrium" to analyze the specific political dynamics of nonhegemonic periods between the breakdown of one ideological order and the emergence of a new one. Although political science has a range theories about periods of hegemony and paradigmatic stability, the periods between stable hegemonies remain distinctly undertheorized. A theoretical concept describing periods of interregnum is offered and applied to the changes in economic ideology and political alignments that followed the breakdown of the liberal order in the interwar period and the postwar Keynesian consensus of the 1970s. The concept is then applied to the current juncture, in which the hegemony of neoliberalism has been shaken by the 2008 financial crisis but no clear successor has emerged.